Beliefs about the smoking effect on COVID-19 as significant factors in smoking cessation efforts - Mochamad Iqbal Nurmansyah; Yustiyani Yustiyani; Narila Mutia Nasir; Deni Wahyudi Kurniawan (Intelektual Pustaka Media Utama, 2023)
Owing to the various scientific evidence linking smoking to the increased risk of developing severe disease and death from the COVID-19 pandemic, now is a critical time for smokers to cut back or quit. This study aimed to analyze the influence of beliefs about smoking effects in relation to COVID-19 and attempts to quit smoking among university student smokers in Jakarta, Indonesia. This study was conducted in three different universities. As many as 198 respondents who were conveniently selected participated in this study. The health belief model (HBM) was adopted to determine the independent variables in this study. Having had a previous infection of COVID-19 influenced the smoking quitting attempts (AOR: 3.87, 1.49–10.0). Moreover, the belief that smoking increased COVID-19 severity, having a friend who reminded the respondents to not smoke during the pandemic, and having the ability to terminate smoking also increased the possibility for respondents to have a quit smoking attempt. However, perceived barriers such as feeling uncomfortable without smoking (AOR: 0.31, 0.15-0.6) were a protective factor against the attempt to quit smoking. Increasing smokers’ confidence to quit smoking and education about the risk of smoking during the pandemic should be intensified to support smokers in successfully quitting the smoking habit.